2012
DOI: 10.1007/s11606-012-2052-2
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer Screening, Diagnosis and Treatment Interventions for Racial and Ethnic Minorities: A Systematic Review

Abstract: OBJECTIVES To systematically review the literature to determine which interventions improve the screening, diagnosis or treatment of cervical cancer for racial and/or ethnic minorities. DATA SOURCES Medline on OVID, Cochrane Register of Controlled Trials, CINAHL, PsycINFO and Cochrane Systematic Reviews. STUDY ELIGIBILITY CRITERIA, PARTICIPANTS AND INTERVENTIONS We searched the above databases for original a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
101
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(102 citation statements)
references
References 45 publications
0
101
0
1
Order By: Relevance
“…[2][3][4][5][6] While many valuable ideas to address racial and ethnic health disparities are being pursued outside of the healthcare system, Finding Answers focuses specifically on what can be accomplished once regular access to healthcare services is achieved. Thus, the reviews focused on interventions that occur in or have a sustained linkage to a healthcare delivery setting; programs that were strictly communitybased were outside the scope of the project.…”
Section: Findings From the Systematic Reviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4][5][6] While many valuable ideas to address racial and ethnic health disparities are being pursued outside of the healthcare system, Finding Answers focuses specifically on what can be accomplished once regular access to healthcare services is achieved. Thus, the reviews focused on interventions that occur in or have a sustained linkage to a healthcare delivery setting; programs that were strictly communitybased were outside the scope of the project.…”
Section: Findings From the Systematic Reviewsmentioning
confidence: 99%
“…Based on low to moderate evidence, the cervical cancer review reported that navigation combined with either education delivered by lay health educators or telephone support can increase the rate of screening for cervical cancer among minority populations. 2 Telephone counseling might also increase the diagnosis and treatment of premalignant lesions of the cervix for minority women. The prostate cancer review focused on the importance of informed decision making for addressing prostate cancer among racial and ethnic minority men.…”
Section: Findings From the Systematic Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite notable advances in surgery, radiotherapy and chemotherapy, even the novel molecular-targeted therapy, the long-term survival of advanced CC patients remains poor due to the high rates of tumor recurrence and distal metastasis (3)(4)(5). To elucidate the development and progression of CC, it is crucial to identify the molecular etiology and molecular mechanisms underlying the progression and metastasis in CC and thus improve therapeutic strategies and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a consistent failure in reaching the most disadvantaged and at risk populations (Glick et al, 2012;Saslow et al, 2012;Simard et al, 2012). An increase in cervical cancer screening between the years 1993 and 2007 has resulted in a decline in cervical cancer related mortality.…”
Section: Introductionmentioning
confidence: 99%